The Validity and Practicality of E-LKPD in the Context of Socio-Scientific Issues Integrated with Scientific Argumentation of Electrolyte and Non-electrolyte Solutions - Fadia, Dwi Rahma; Gazali, Fauzana; Daswarman, Daswarman (Entalpi Pendidikan Kimia, 2025)
Scientific argumentation skills play a crucial role in fostering 21st-century thinking skills and can be enhanced through socio-scientific contexts. Nonetheless, in the topic of electrolyte and non-electrolyte solutions, these skills have yet to be fully developed due to the absence of supportive learning contexts and teaching materials. Thus, this research aims to develop teaching materials in the form of an e-LKPD based on Socio-Scientific Issues (SSI) integrated with scientific argumentation for electrolyte and non-electrolyte solution topics in SMA/MA chemistry, as well as to assess their validity and practicality. This study employs Educational Design Research (EDR) with the Plomp development model. The validation process involved five validators, consisting of three lecturers and two teachers. The practicality test was carried out by nine students from SMAN 12 Padang. The validation results showed a score of 0.9, indicating a valid category, while the practicality test received student responses of 93% (very practical) and teacher responses of 89% (very pract1ical)..